The dark side of mRNA translation and the translation machinery in glioblastoma - Montiel-Dávalos, Angélica; Ayala, Yeniffer; Hernández, Greco (Frontiers in Cell and Developmental Biology, 2023)
Among the different types of cancer affecting the central nervous system (CNS), glioblastoma (GB) is classified by the World Health Organization (WHO) as the most common and aggressive CNS cancer in adults. GB incidence is more frequent among persons aged 45-55 years old. GB treatments are based on tumor resection, radiation, and chemotherapies. The current development of novel molecular biomarkers (MB) has led to a more accurate prediction of GB progression. Moreover, clinical, epidemiological, and experimental studies have established genetic variants consistently associated with the risk of suffering GB. However, despite the advances in these fields, the survival expectancy of GB patients is still shorter than two years. Thus, fundamental processes inducing tumor onset and progression remain to be elucidated. In recent years, mRNA translation has been in the spotlight, as its dysregulation is emerging as a key cause of GB. In particular, the initiation phase of translation is most involved in this process. Among the crucial events, the machinery performing this phase undergoes a reconfiguration under the hypoxic conditions in the tumor microenvironment. In addition, ribosomal proteins (RPs) have been reported to play translation-independent roles in GB development. This review focuses on the research elucidating the tight relationship between translation initiation, the translation machinery, and GB. We also summarize the state-of-the-art drugs targeting the translation machinery to improve patients´ survival. Overall, the recent advances in this field are shedding new light on the dark side of translation in GB.